A common justice : the legal allegiances of Christians and Jews under early Islam - Simonsohn, Uriel I., 1971- (Divinations., 2011)
Focusing on the late seventh to early eleventh centuries in the region between Iraq in the east and present-day Tunisia in the west, this study explores the multiplicity of judicial systems that coexisted under early Islam to reveal a complex array of social obligations that connected individuals across confessional boundaries.